Kurikulum Sastra Berbasis Teknologi pada Era Digital - Kami, Kanisius; Artika, I Wayan (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to describe the technology-based literature curriculum in the digital era. This type of research is library research with the object of research is technology-based literary curriculum in the digital era. The data of this research is in the form of verbal description that contains information about technology-based literature curriculum in the digital era, which is related to the underlying principles and alternative concepts of technology-based literature curriculum in the digital era. The data was obtained from sources such as books, research articles, and scientific journal proceedings. The data sources were selected based on considerations the credibility of the owner of the idea or publication. the accuracy of the source, especially regarding novelty, detail, and completeness. Objective balanced and acceptable, and (d) the availability of complete information about the data source for tracking and communication. The data analysis technique is content analysis or content a sis from the data source to the conclusion. The results in this study found several basic elements that can be accommodated in a technology-based literature curriculum in the digital era, including the use of digital media, interactive learning, e-learning platforms, the use of learning aids, digital skills development, and digital creativity